Mental Health Literacy of University Students - Rachella Ryandra Fitri (Department of Psychology, Universitas Negeri Yogyakarta, 2019)
The purpose of this study is to observe: (1) Gender difference in mental health literacy of Yogyakarta State University students and (2) Differences in mental health literacy of Yogyakarta State University students based on vignette character’s gender. The type of this study was factorial survey. In this study, respondents were presented with short descriptions called vignette that were constructed and contained elements that had been manipulated by the researcher to control certain variables, namely gender and mental disorders that the characters had. Then, subjects were asked to answer closed questions (Mental Health Literacy Test) based on the vignettes. The subjects in this study were 377 undergraduate students from Yogyakarta State University. The sampling techniques used in this study were cluster random sampling and incidental sampling. Chi-Square was performed to analyze the data. The results of this study indicated that: (1) There were gender differences in mental health literacy aspect positive attitudes toward professional help where more male respondents did not recommend seeking professional help for depression (2) There were differences in mental health literacy aspects knowledge about the causes of mental disorders and positive attitudes towards professional help based on gender vignette characters for depression.